2-Deoxy-D-Glucose and its Derivatives for the COVID-19 Treatment: An Update - Huang, Zoufang; Chavda, Vivek P.; Vora, Lalitkumar K.; Gajjar, Normi; Apostolopoulos, Vasso; Shah, Nirav; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
Treatment choices for the “severe acute respiratory syndrome‐related coronavirus‐2 (SARS‐CoV‐2)” are inadequate, having no clarity on efficacy and safety profiles. Currently, no established intervention has lowered the mortality rate in the “coronavirus disease 2019 (COVID‐19)” patients. Recently, 2-deoxy-D-glucose (2-DG) has arisen as a polypharmacological agent for COVID-19 therapy owing to its influence on the glycolytic pathway, interaction with viral proteins, and anti-inflammatory action. In May 2020, the Indian drug regulatory authority approved 2-DG as an emergency adjunct therapy in mild to severe COVID-19 patients. Clinical studies of 2-DG corroborate that it aids in quicker recovery of hospitalized patients and decreases supplemental oxygen. Herein, we describe the development process, synthesis, mechanism of viral eradication, and preclinical and clinical development of 2-DG and its derivatives as molecularly targeted therapeutics for COVID-19 treatment.